Nano/ultrafine grained immiscible Fe-Cu alloy with ultrahigh strength produced by selective laser melting. Issue 6 (3rd June 2021) - Zafari, A.; Xia, K.
Abstract : A nano/ultrafine grained immiscible Fe-Cu alloy was produced using selective laser melting (SLM) with an average grain size of 250 nm and many 50–100 nm, the finest ever achieved using additive manufacturing (AM). The substantial grain refinement was attributed to liquid separation, monotectic reaction and solid-state phase transformations upon cyclic heating. Cu particles of ∼5 nm in size and ∼10 nm in spacing were contained in some grains, resulting in dispersion strengthening which, together with grain boundary strengthening, led to a significant increase in the yield strength from ∼400 MPa in an SLM-fabricated Fe to ∼900 MPa in Fe-Cu. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: Nano/ultrafine Fe grains containing Cu particles of 5 nm in size and 10 nm in spacing were achieved by SLM of Fe-Cu, resulting in an ultrahigh strength material.